Synthesis and performance of PAFS coagulant derived from aluminium dross - Li, Shiyi; Sobri, Shafreeza (Universiti Putra Malaysia Press, 2022)
Polymerised aluminium ferric sulphate (PAFS) was prepared from aluminium dross as a coagulant in wastewater treatment. The effects of leaching time, leaching temperature, and sulfuric acid concentrations on the turbidity removal of the wastewater were investigated, and the optimum conditions were determined using response surface methodology. The results showed that the optimum PAFS preparation conditions were at a leaching time of 60 minutes, a leaching temperature of 65°C, and a sulfuric acid concentration of 1 mol/L. Furthermore, experiments were performed to investigate the effect of coagulant dosages using the PAFS prepared under the optimum leaching conditions, settling time and initial pH of the wastewater on the turbidity removal efficiency. As a result, it was found that the optimum coagulation conditions for PAFS coagulants were at a settling time of 15 minutes, coagulant dosage of 0.5g, and raw water pH 8. Under these optimum conditions, the turbidity removal efficiency of the wastewater was 91.45%. The purpose of this study was to investigate the possibility of aluminium dross utilisation as a coagulant agent for wastewater treatment. Therefore, it can be concluded that PAFS prepared by leaching metal oxides from aluminium dross is an effective wastewater coagulant.